Carbonate and organic carbon content in the recent sediments of Elefsis bay as indicators for the paleoenviromental evolution of the system. - Petropoulos, A.; Androni, A.; Ntamkarelou, T.; Anagnostou, Ch. (Bulletin of the Geological Society of Greece, 2013)
During the Holocene period Elefsis bay acted as a semi-enclosed system obstructing water circulation. In some areas, sampling has revealed the problems of anoxia that prevails in the bay, which has been worse during the summer months. Analyses undertaken in a core from the bay of Elefsis showed notable changes in carbonate and organic material, which prove the paleo-environmental evolution of the bay. Such changes of carbonate are due to the different deposition of calcium carbonate from biogenic source (probably and from inorganic source). The variation of organic carbon is still a factor of limited water circulation in the bay.